It says it’s 73. But how can that be when you go left to right first doing order of operations. Times and divide first, then add. So you get 9.
9 Answers

What Is 9 X 9

(9*9) + (9/9) – 9
= 81 + 1 – 9
= 73
If you ignore the Order of Operations and just read from left to right:
9 * 9 + 9 / 9 – 9
= 81 + 9 / 9 – 9
= 90 / 9 – 9
= 10 – 9
= 1
Where did you get 9?

Multiplication first, that gives you 81 + 9/9 9
Division is next, that gives you 81 + 1 9
Then addition, to get 82 – 9
Subtraction gives you 73.

using PEMDAS, it’s
81 + 1 – 9 =
82 – 9 =
73.

73 is correct as written.
9 × 9 + 9 / 9 – 9
Multiply first.
81 + 9 / 9 – 9
Divide next.
81 + 1 – 9
Add next.
82 – 9.
Now subtract. 73 is the right answer.
————————————
To get 9 you’d have to parenthesise 9 + 9:
9 × (9 + 9) / 9 – 9
Add first; you must clear all parentheses/brackets first according to PEMDAS.
9 × 18 / 9 – 9
Multiply next.
162 / 9 – 9
Divide next.
18 – 9
Now subtract. This answer is 9.

(9×9)+9 (99)
81+9

73

81+1 9
73

I got 1. going from left to right if you have multipication first